Development problems of innovative activity in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
In development of a country the main directions and objectives is the creation of an economy aimed at innovative development. To date, the main problem of increase competitiveness is the creation of required innovation policy. Economic growth is achieved by formation of an effective innovation system with the mechanism of the relationship between business, science and education. In Kazakhstan, the State is doing the program and the conditions for innovation development. The feature of innovative development of our country can be called a low level of activity of manufacturing companies in the development and research of innovative products, limiting the purchase of innovative products and projects developed abroad. The disadvantages of the national innovation system also include the low level of participation in the development of innovative products and projects, which is an indicator of low innovation activity of enterprises.
Keywords: innovation activity; innovation; national innovation system; innovative development; new product.